2006
DOI: 10.1172/jci27890
|View full text |Cite|
|
Sign up to set email alerts
|

Glucosylceramide synthase is an essential regulator of pathogenicity of Cryptococcus neoformans

Abstract: The pathogenic fungus Cryptococcus neoformans infects humans upon inhalation and causes the most common fungal meningoencephalitis in immunocompromised subjects worldwide. In the host, C. neoformans is found both intracellularly and extracellularly, but how these two components contribute to the development of the disease is largely unknown. Here we show that the glycosphingolipid glucosylceramide (GlcCer), which is present in C. neoformans, was essential for fungal growth in host extracellular environments, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
270
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(277 citation statements)
references
References 43 publications
(57 reference statements)
6
270
0
1
Order By: Relevance
“…A variety of studies have recently shown that affecting enzymes involved in these sphingolipid biosynthetic pathways using inhibitors or gene deletion can attenuate the virulence of fungal pathogens such as, Candida albicans, Cryptococcus neoformans and Aspergillus spp. [13][14][15]. Several natural inhibitors of fungal GlcCer synthesis have been described to exhibit a potent antifungal activity [16][17][18].…”
mentioning
confidence: 99%
“…A variety of studies have recently shown that affecting enzymes involved in these sphingolipid biosynthetic pathways using inhibitors or gene deletion can attenuate the virulence of fungal pathogens such as, Candida albicans, Cryptococcus neoformans and Aspergillus spp. [13][14][15]. Several natural inhibitors of fungal GlcCer synthesis have been described to exhibit a potent antifungal activity [16][17][18].…”
mentioning
confidence: 99%
“…Biological functions of GlcCer in fungi have been studied through gene deletion and inhibitory approaches. The interruption of any steps of the GlcCer biosynthetic pathway leads to a defect in growth, morphology and virulence in yeast and filamentous fungal pathogen [23][24][25]. Among Aspergillus species, GlcCer biosynthesis and functions have been mainly investigated in A. nidulans, a model filamentous fungus.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Plant and mammalian fungal pathogens, deficient in GlcCer, are less virulent [24,27,29,78,79]. The role of GlcCer, required for the full virulence of human fungal pathogen C. neoformans has been more investigated [25]. GlcCer deficient yeast does not present growth defect in acidic pH but do not growth at a neutral/alkaline pH which is essential for the fungal growth in host extracellular environment [25].…”
Section: Role Of Spls In Host-pathogen Interaction and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, C. neoformans is a facultative intracellular pathogen capable of surviving not only in the extracellular environment of the alveolar spaces but also intracellularly within AMs (Feldmesser et al, 2000). Thus, when AMs are unable to kill intracellular C. neoformans, internalization of C. neoformans is detrimental to the host as it provides a protective environment that promotes survival and can exacerbate the dissemination from the lung to other organs (Chrétien et al, 2002;Goldman et al, 2000;Kechichian et al, 2007;Levitz et al, 1999;Luberto et al, 2003;Rittershaus et al, 2006). Therefore, it is important to our understanding of the pathogenesis of C. neoformans to define the host factors modulating the effector functions of AMs, specifically phagocytosis, in order to develop new anticryptococcal therapeutic regiments.…”
Section: Introductionmentioning
confidence: 99%